Shifting the Surgical Residency Match to a 100% Virtual Interview Format During the COVID-19 Pandemic, How has It Affected Placement Into Surgical Training Programs?. Issue 4 (April 2023) - Newsome, Kevin; Selvakumar, Sruthi; McKenny, Mark; Elkbuli, Adel
Introduction: The AAMC transitioned to virtual interview formats for the 2020-2021 residency match. This study aims to examine the impact of the 100% virtual interview format for the 2020-2021 residency match on both application and match changes for multiple surgical specialties, including neurosurgery (NS), orthopedic surgery (OS), plastic surgery (PS), general surgery (GS), thoracic surgery (TS), and vascular surgery (VS). Methods: Cross-sectional study comparing application and match changes between the in-person 2019-2020 and virtual 2020-2021 residency match cycles for different surgical specialties. Results: There was an overall increase in the number of applicants for 5 of the surgery specialties but not VS, and an overall increase in the number of applications per residency program across all specialties. The average number of applications per applicant also increased, except in TS. There were no major match changes except in TS, which saw an increase in number of spots filled by MDs to nearly 100% from 84.2% in the previous cycle. Conclusion: The switch to the 100% virtual 2020-2021 residency match interview format was associated with an overall increase in the number of applications per program and number of applications per applicant across multiple surgical specialties. There was a decrease in the number of applicants to VS and an increase in the number of applications per applicant. The switch to a virtual interview format in 2020-2021 was also associated with an increase in TS spots filled by MDs to almost 98%, increasing the already concerning TS match disparity for DO and IMG applicants.